Comparing survival in patients with chronic kidney disease across three countries – Results from the study of heart and renal protection‐extended review. Issue 1 (9th November 2022) - Talbot, Benjamin; Cass, Alan; Walker, Robert; Hooi, Lai; Jardine, Meg; Jun, Min; Rogers, Kris; Sukkar, Louisa; Smyth, Brendan; Gallagher, Martin
Abstract: Aim: This study examined whether survival and causes of death differed between participants enrolled from Australia (AUS), Malaysia (MYL), and New Zealand (NZ) in extended follow‐up of the Study of Heart and Renal Protection (SHARP), a randomized controlled trial (RCT) of participants with moderate to severe chronic kidney disease comparing placebo to combination therapy with Simvastatin and Ezetimibe. Methods: All participants alive at final SHARP study visit in participating centres were eligible for inclusion. Consenting participants were re‐enrolled following final SHARP Study visit and followed for 5 years. Data collection included: significant medical events, hospital admissions and requirement for kidney replacement therapy. Data linkage was performed to national kidney and mortality registries. The primary outcome was all‐cause mortality compared across the three countries. Results: The SHARP trial randomized 2029 participants from AUS (1043/2029, 51%), MYL (701/2029, 35%), and NZ (285/2029, 14%), with 1136 participants alive and eligible for extended follow‐up at the end of SHARP. In multivariable analysis, risk of death was increased for participants in MYL (HR 1.37, 95% CI 1.17–1.61, p  < .001) and NZ (HR 1.28, 95% CI 1.04–1.57, p  = .02) when compared to AUS participants. Adjustment for kidney transplantation as a competing risk did not explain the variation seen between countries. Conclusion: This study allows a better understanding of the differences in long‐term mortality risk across participants from AUS, MYL, and NZ in extended follow‐up of the SHARP study and demonstrates the feasibility and value of extended follow‐up of participants enrolled in RCTs. Summary at a glance: This study has identified differences in long‐term mortality risk between participants enrolled from Australia, Malaysia and New Zealand in extended follow‐up of the Study of Heart and Renal Protection (SHARP), a randomized controlled trial comparing placebo to combination therapy with Simvastatin and Ezetimibe in participants with chronic kidney disease.